ChemInform Abstract: Fragmentation of Bicyclic γ‐Silyloxy‐β‐hydroxy‐α‐diazolactones as an Approach to Ynolides. Issue 52 (29th December 2014) - Bayir, Ali; Brewer, Matthias
Abstract The presented method gives access to 10 and 11 membered ynolides, which are the smallest reported to date.